The role and challenges of watercolor art in the integration of environmental psychology and social psychology from an interdisciplinary perspective - Dong Li (Environment and Social Psychology, 2025)
This study adopts an interdisciplinary perspective to systematically explore the operational mechanisms, effect characteristics, and practical challenges of watercolor art in the integration of environmental psychology and social psychology. Through a mixed-method approach combining literature review, experimental research, and field investigation, an 18-month longitudinal study was conducted with 745 participants, employing standardized psychological measurement instruments to assess the multidimensional psychological effects of watercolor art.The findings reveal that: In the environmental psychology dimension, watercolor art significantly facilitates stress recovery (42% reduction), attention restoration (37% improvement), and emotion regulation (54% enhancement), achieving psychological restoration functions through a three-stage pathway of "soft fascination-deep engagement-cognitive reconstruction." In the social psychology dimension, watercolor art effectively enhances social interaction quality (48% increase), strengthens community identity construction (sense of belonging +62%, place attachment +87%), and promotes social attitude transmission (attitude change +217%), operating through a triple pathway of "aesthetic pleasure-emotional arousal-memory consolidation."The key innovation lies in revealing the cross-dimensional synergistic enhancement mechanism across environmental-social dual dimensions (average +24%, η²=0.37), demonstrating that the integrated effects significantly exceed linear additive expectations, thereby providing empirical support for establishing a triadic integration theoretical framework of "environment-society-individual." The study also identifies differentiated response patterns among diverse groups: elderly populations exhibit significant advantages in stress recovery (8.5 points), artistic experience demonstrates compensatory effects for socioeconomic disadvantages (low-education groups +58%), and rural communities display "reverse advantages" in social belonging (+9%).The research confronts challenges including interdisciplinary methodological integration, long-term effect tracking, and cultural applicability. Future directions recommend exploring deeper mechanisms through neuroimaging techniques, conducting randomized controlled trials to verify intervention effects, expanding cross-cultural comparative research, and advancing both theoretical deepening and applied transformation in the psychology of watercolor art.